The Study on the Coronavirus Pandemic Using Human Rights and Human Security Approach - Indah Pangestu Amaritasari (Badan Strategi Kebijakan Hukum, 2022)
In March 2020, The World Health Organization (WHO) finally announced a coronavirus or Covid-19 disease outbreak as a pandemic. According to WHO, the status of a pandemic is determined if a new disease has not had an antidote against the spread of the virus in regions of the world. The virus attacked individuals and no doubt the impact on people is significant, which relates to the security of the people and human rights aspects. The article explores the argumentative basis of human security and further analyzes the problem, strategy and needs in the lens of human rights related to pandemic in the framework of human security. It aims to analytically describe human security approaches in relation to the COVID-19 with human rights perspective through the common pattern of threat identified worldwide and plausible strategies based on literature study. The state strategy addressed in the article exists as a set of examples of best practices and/or critics toward the policy with materials provided by journals. The article uses a qualitative approach with a systematic literature study based on human security framework with human-right analysis and results in a generic set of human security frameworks for COVID-19 with the perspective of human rights.